Estimating aboveground biomass in native forests using remote sensing data combined with spectral radiometry - Manrique, Silvina Magdalena (2012)
The management of forests as carbon (C) reservoirs could be a valid strategy for mitigating global climate change. In Salta, Argentina, there is an urgent need for updated information on biomass stocks in order to assess the C sequestering and release made by native forests. We studied three ecosystems (Chaco, Yungas and shrubland) by combining different data: a) field-estimated above-ground biomass (AGB); b) field-spectral data, and c) spectral data from remote sensing. AGB was estimated through allometric equations. Radiometric measurements were synthesized into a set of spectral vegetation indices (VI). The satellite data was calibrated with those obtained through field radiometry, allowing us to find a predictive AGB model which indicates an AGB average of 85 ± 250 t.ha-1 for the center of the province of Salta. The model which was finally selected increases the level of estimate detail made at the national level and will allow the monitoring of such data.